The Existence of Weak Solutions of a Higher Order Nonlinear Eilliptic Equation (Communications in Mathematical Research, 2019)
In this paper, we show the existence of weak solutions for a higher order nonlinear elliptic equation. Our main method is to show that the evolution operator satisfies the fixed point theorem for Banach semilattice.